Regioselectivity significantly impacts microsomal glucuronidation efficiency of R/S-6, 7-, and 8-hydroxywarfarin. (3rd April 2019) - Kim, So-Young; Jones, Drew R.; Kang, Ji-Yeon; Yun, Chul-Ho; Miller, Grover P.
Abstract: Coumadin (R/S-warfarin) metabolism plays a critical role in patient response to anticoagulant therapy. Several cytochrome P450s oxidize warfarin into R/S-6-, 7-, 8-, 10, and 4′-hydroxywarfarin that can undergo subsequent glucuronidation by UDP-glucuronosyltransferases (UGTs); however, current studies on recombinant UGTs cannot be adequately extrapolated to microsomal glucuronidation capacities for the liver. Herein, we estimated the capacity of the average human liver to glucuronidate hydroxywarfarin and identified UGTs responsible for those metabolic reactions through inhibitor phenotyping. There was no observable activity toward R/S-warfarin, R/S-10-hydroxywarfarin or R/S-4′-hydroxywarfarin. The observed metabolic efficiencies ( V max / K m ) toward R/S-6-, 7-, and especially 8-hydroxywarfarin indicated a high glucuronidation capacity to metabolize these compounds. UGTs demonstrated strong regioselectivity toward the hydroxywarfarins. UGT1A6 and UGT1A1 played a major role in R/S-6- and 7-hydroxywarfarin glucuronidation, respectively, whereas UGT1A9 accounted for almost all of the generation of the R/S-8-hydroxywarfarin glucuronide. In summary, these studies expanded insights to glucuronidation of hydroxywarfarins by pooled human liver microsomes, novel roles for UGT1A6 and 1A9, and the overall degree of regioselectivity for the UGT reactions.